Impact on quality of life in acne patients attending the tertiary care center in Saurashtra region of Gujarat - N., Raghavon U.; Gangawala, Vaishnavi; Bhuptani, Neela V.; Patel, Bharti K. (International Journal of Research in Dermatology, 2022)
Background: Acne vulgaris is a common chronic skin disorder that is defined by inflammation of the pilosebaceous units and has a variety of symptoms and treatment options. Acne is very prevalent among teenagers, and it can linger far into adulthood. In this study, the dermatological life quality index was assessed in acne vulgaris patients. Methods: This is a hospital based prospective cross-sectional questionnaire study done on acne vulgaris patients attending the dermatology outpatient department in a tertiary care hospital in Saurashtra region, Gujarat. Quality of life (QoL) was measured using both acne specific (Cardiff acne disability index (CADI)) questionnaire and skin disease specific (Dermatology life quality index (DLQI)) questionnaire. Results: In our study, women outweighed men (M:F ratio=1:1.43). Those between the ages of 15 and 20 were the most affected. The average DLQI score was 5.5947. The vast majority had a ’minor impact’ on QoL. Females had a lower QoL than males. In general, grade 2 acne was the most common kind of acne. Males were more likely to have grade 3 acne. The majority of the patients (84%) experienced embrassement or heightened self-consciousness as a result of their acne. Conclusions: Our research reveals that acne has a detrimental influence on QoL, demonstrating the need for a comprehensive approach to treating the body and mind for overall well-being.